ADAPTING IPV6 AND 6LOWPAN OVER WIFI-BASED AODV MANETS FOR IOT APPLICATIONS - Afaq Ahmed; Shafqat Ali; Syed Naseem Abbas; Aqsa Khursheed; Hina Shafique; Syeda Naila Batool; Ghulam Gilanie (Spectrum of Engineering Sciences, 2025)
Ad-hoc On-demand Distance Vector (AODV) is a routing protocol for Mobile Ad-hoc Networks (MANETs) to facilitate communication between wireless nodes in a dynamic, infrastructure-less environment. It was initially designed to use IPv4, however, with the evolution and wide adoption of IPv6 as the next generation network protocol, especially for the Internet of Things (IoT) envoirnment, there is a need to adapt AODV for use in IPv6 MANETs and investigate its suitability for deployment of IoT nodes under mobility, where several mobile sensor nodes may need to gather data and collaborate dynamically. Additionally, AODV can also be used to facilitate multi-hop communication between vehicles on the road, enabling applications such as cooperative collision avoidance, traffic management, and infotainment services. The evaluation of IPv6-based AODV needs an extensive simulation study in a network simulator, such as NS-3. We have, therefore, extended NS-3 by implementing and testing a model of AODV in NS-3 that operates using IPv6 protocol; currently, NS-3 has an IPv4-based AODV module. The adaptation of AODV to IPv6 requires mapping its complete functionality from IPv4 to IPv6, including node addressing, replacement of broadcast with multicast, features specific to Internet Control Message Protocol (ICMPv6) such as duplicate address detection (DAD), and address resolution using neighbor solicitation and neighbor advertisement messages, instead of the traditional Address Resolution Protocol (ARP). We designed our experiments to extensively test our model for small to large-scale deployment of nodes, low mobility, and small-size frequent messages, to model the IoT environment. Our simulation study involved verifying the correct functionality of AODV with IPv6, along with comparing the protocol performance of AODV in IPv4 and IPv6-based WiFi MANETs. Our results indicate that AODV operation with IPv6 does not significantly degrade the network performance in comparison with IPv4; however, an increase in control overhead was observed due to large IPv6 headers. We, therefore, extended our experiments to compress IPv6 headers by incorporating 6LoWPAN as a shim layer above the WiFi MAC. 6LoWPAN has originally been designed for IEEE 802.15.4 to carry large IPv6 packets inside small frames of Low-Rate Wireless PAN (LR-WPAN) technology. By employing header compression of 6LoWPAN, we were able to reduce the control overhead of IPv6-based AODV. As a result of this work, we have extended NS-3 functionality by implementing an additional module of AODV protocol based on IPv6, tested its correct functionality in WiFi-based MANETs, and compared the network performance of IPv4-based AODV with that of AODV with IPv6 and 6LoWPAN for possible application in IoT environment.